2018
DOI: 10.1016/j.nedt.2018.03.023
|View full text |Cite
|
Sign up to set email alerts
|

How do we facilitate international clinical placements for nursing students: A cross-sectional exploration of the structure, aims and objectives of placements

Abstract: International clinical placements in the Asia region appear to vary greatly from one education institution to the next with no clear consensus from either this study's findings or the literature on which structure, support and assessments lead to greater student learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 23 publications
2
12
0
2
Order By: Relevance
“…Kokko asserts that for the development process required to gain true cultural competence, longer exchanges are necessary. This is supported by other researchers whose analysis of the length of exchanges ranged from eight days to 21 days total (Browne and Fetherston 2018). This five-week study exceeded these shorter exchanges considerably yet host country staff rightly felt it was still an insufficient length of time for the students to understand the rich complex culture and therefore limited their ability to experience a profound cultural shift.…”
Section: Host Countries' Perceptions "Canadian Students Have Heart"supporting
confidence: 53%
“…Kokko asserts that for the development process required to gain true cultural competence, longer exchanges are necessary. This is supported by other researchers whose analysis of the length of exchanges ranged from eight days to 21 days total (Browne and Fetherston 2018). This five-week study exceeded these shorter exchanges considerably yet host country staff rightly felt it was still an insufficient length of time for the students to understand the rich complex culture and therefore limited their ability to experience a profound cultural shift.…”
Section: Host Countries' Perceptions "Canadian Students Have Heart"supporting
confidence: 53%
“…Other studies ( 10 - 12 ) consider promising the curricular proposal that works the competences from the early insertion of the student in the scenarios of practices. This process facilitates the integration of teaching-service-community by mediating the student’s contact with the unique and plural challenges of the profession.…”
Section: Introductionmentioning
confidence: 99%
“…International experiences can also provide students with skill development in foreign languages (Garone & Van de Craen, 2017;Read, 2011) and achieve clinical competencies with different cultural groups and varying clinical areas. International experiences can be transformative for students and educators alike, helping them to grow their global citizenship (Browne & Fetherston, 2018) and attempting to raise quality standards to meet the global demand in nursing and health care. Last, students might better appreciate the realities of where they live and work on return home (Pereira et al, 2018).…”
Section: The Growth Of Internationalization In Nursingmentioning
confidence: 99%
“…We have found that working across borders to design and develop international experiences for students is often a complex, labor-intensive, and sometimes expensive venture, and these matters are supported by the international literature. International exchanges require significant commitment from the educational institutions, as well as the personal and professional commitment of educators who need to be involved in learning about international experiences themselves and facilitating such experiences for students (Browne & Fetherston, 2018). A major problem is that, to date, institutions have minimally supported faculty development related to teaching that supports intercultural development (Williams & Lee, 2015).…”
Section: Facilitating International Experiences: Practical Strategiesmentioning
confidence: 99%